Magnetic ordering induced by interladder coupling in the spin-1/2 Heisenberg two-leg ladder antiferromagnet C9H18N2CuBr4 - Hong, Tao; Schmidt, Kai Phillip; Coester, K.; Awwadi, F. F.; Turnbull, M. M.; Qiu, Y.; Rodriguez-Rivera, J. A.; Zhu, M.; Ke, X.; Aoyama, C. P.; Takano, Y.; Cao, Huibo; et al. (Physical Review B, 2014)
We present specific-heat and neutron-scattering results for the S = 1/2 quantum antiferromagnet (dimethylammonium)(3,5-dimethylpyridinium)CuBr4. The material orders magnetically at T-N = 1.99(2) K, and magnetic excitations are accompanied by an energy gap of 0.30(2) meV due to spin anisotropy. The system is best described as coupled two-leg spin-1/2 ladders with the leg exchange J(leg) = 0.60(2) meV, rung exchange J(rung) = 0.64(9) meV, interladder exchange J(int) = 0.19(2) meV, and an interaction-anisotropy parameter lambda = 0.93(2), according to inelastic neutron-scattering measurements. In contrast to most spin ladders reported to date, the material is a rare example in which the interladder coupling is very near the critical value required to drive the system to a Neel-ordered phase without the assistance of a magnetic field.